Stan bezpieczeństwa terenów przygranicznej Lubelszczyzny po delimitacji granicy państwowej w latach 1944-1947. Próba analizy problemu - WAWRYNIUK, Andrzej (Historia i Świat, 2013)
The most common reason for armed conflicts outbreak is the desire to expand the territories. “The scars of the history” – the new areas which are the results of such actions create many problems of social or cultural nature. Due to the fact that minority population lives at the crossroads of two states causes that the most significant difficulty is safety. In the paper an overview of the Lublin border ethnic relations, including the Polish - Ukrainian relations during the Second World War and the tragic period just after its end are presented. What is empathized is the fact that the mentioned period was a time when in the common Polish-Ukrainian history numerous examples of kindness, compassion, or even good neighborly relations occurred. These gestures proved peaceful coexistence between the two nations was possible. An unknown number of Red Army soldiers, maybe a small group, committed crimes on Polish territory. The fact is important and verified with a specific documents. The used scans of documents and photos come from the New Acts Archives of Tomaszow Lubelski and the Regional Museum in Lublin.